Transformational Leadership Challenges: Building Employee Performance through the Establishment of Organizational Work Culture at PT. Food Station Tjipinang Jaya Jakarta - Beni Edmunandar; Susilo Toto Raharjo (Journal La Sociale, 2023)
This research aims to determine employee performance influenced by transformational leadership through organizational work culture. Utilizing quantitative research methods with primary data, the population for this study included all 180 employees of PT Food Station, with 124 employees at the time of the research. Data collection employed a closed questionnaire using a Likert scale of 1-5. The data analysis utilized Structural Equation Modeling (SEM) with an alternative method, namely Partial Least Square (PLS). The research results demonstrate that employee performance is significantly influenced by transformational leadership. Organizational work culture is also significantly influenced by transformational leadership. Furthermore, employee performance has been proven to be significantly influenced by organizational work culture. The organizational work culture has been shown to significantly mediate the influence of transformational leadership on employee performance. The research results also indicate that organizational work culture functions as a significant mediator, connecting the positive influence of transformational leadership with employee performance. Therefore, it can be concluded that transformational leadership not only directly influences employee performance but also, through the formation of a positive organizational work culture, creates a deeper influence on employee performance outcomes.